Kesadaran Hukum Tentang Kewajiban Halal Self Declare Bagi Produk Kopi pada Coffee Shop di Medan Pancing - Falya Syahara; Zulham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Coffee shops in the city of Medan have not fully carried out Halal Self Declare, even though the halal product guarantee as regulated in the JPH Law stipulates halal self declare obligations for MSMEs in accordance with the regulations stipulated by the JPH Law in article 4, namely the obligation to be halal certified for products circulating and traded in the area. Indonesia is valid for 5 (five) years starting when the law comes into force. This research aims to explain and analyze legal awareness regarding the obligation to self-declare halal coffee products for coffee shops as MSMEs in Medan City. This Halal Self Declare Obligation aims to avoid halal uncertainty and misleading information for consumers. This research uses empirical juridical research methods, namely related to juridical matters and facts regarding the Halal Self Declare obligation for coffee products at coffee shops in Medan Pancing. The research results show that based on the author's observations of several coffee shops in Medan Pancing, there are 8 coffee shops that do not have a halal certificate and claim that their products are halal without any legality. In general, business actors do not know the procedures in the Self Declare scheme, but coffee shops are expected to comply with regulations and the government's role in providing direction for the implementation of Self Declare product halal certificates for MSMEs in Medan Pancing.